IMPACT OF CHEMICAL REACTION ON MHD BOUNDARY LAYER FLOW OF NANOFLUIDS OVER A NONLINEAR STRETCHING SHEET WITH THERMAL RADIATION HAAR WAVELET COLLOCATION METHOD - N, MAHESH KUMAR; Awati, Vishwanath B; Goravar, Akash (Media Mesin: Majalah Teknik Mesin, 2024)
In this paper, we investigate the effects of chemical reaction and thermal radiation on MHD boundary layer fluid flow of nanofluid moving over a nonlinearly stretching sheet through semi-numerical approach. The nanofluid physical model of the problem comprises with effects of thermophoresis, radiation and chemical reaction parameters. The mathematical model scrutinizes mass, momentum, heat transfer and concentration equations are reduced to couple nonlinear ordinary differential equations over infinite domain using proper similarity variables. Haar wavelet collocation method is used to solve the resulting equations. The obtained results are compared with available numerical findings and are comparable which confirms and verifies the wavelet method. The effects of various non-dimensional parameters on the rate of heat and mass transfer are depicted through tables and graphs. It predicts that, the local Sherwood number increases with increase in the parameters of Brownian motion and thermophoresis. For both temperature and volume fraction profiles decreases due to an increase in the Schmidt number.